Analysis of The Effectiveness of The Filling Machine Kalix Plastic 501 using The of Overall Equipment Effectiveness (OEE) Method at PT. XYZ - Widiyati, Khusnun; Pangestu, Panji (Journal of Emerging Supply Chain, Clean Energy, and Process Engineering, 2024)
This study discusses the effectiveness of the Kalix Plastik 501 Filling machine at PT. XYZ with the Total Productive Maintenance (TPM) approach, namely by examining the Six Big Losses factors on the machine to increase the Overall Equipment Effectiveness (OEE) value. The TPM program aims to produce effectiveness in all production by participating in productive, proactive and planned activities. TPM effectiveness can be done by measuring the OEE value, where the performance of a machine can be said to be optimal if it has an OEE international standard value of > 85%. This paper provides valuable information about the performance of production machines and offers possible solutions to increase their efficiency. Based on the results of data calculations, it is known that the average value of the effectiveness of the Kalix Plastic 501 filling machine at PT. XYZ is 57,05%, meaning that this value is below the standard OEE value. Furthermore, it is known that the losses that cause low OEE values in this study are the result of deceleration loss (23%), setup and adjustment (14,78%), idle and minor stoppages (7,41%), breakdown failure (3,91%), scrap loss (0.24%), and yield loss (0%). The six losses occurred due to human factors such as lack of manpower and not following work instructions, machine factors such as sensor errors, broken filling valves, and procedural factors such as lack of PM schedules and product operations not continuing.